Ammonium Sulfide Surface Treatment of Electrodeposited p-Type Cuprous Oxide Thin Films - Jayathilaka, K.M.D.C.; Kapaklis, V.; Siripala, W.; Jayanetti, J. K. D. S. (My University, 2014)
The effects of ammonium sulfide surface treatment on electrodeposited p-type polycrystalline cuprous oxide (Cu2O) thin films deposited on Ti substrates were studied. The structural and morphological properties of the films were investigated using scanning electron microscopy, x-ray diffraction, and energy-dispersive x-ray spec troscopy. The changes in the conductivities and photocurrents of the films after the ammonium sulfide treatment were determined. Films that had undergone the ammonium sulfide treatment showed reduced resistivities, enhanced spectral photoresponses, and enhanced current-voltage characteristics. The results showed that ammo nium sulfide treatment improved the peak output current of the p-type Cu2O films by about 400% compared with those of bare Cu2O films. This improvement is attributed to the passivation of defects in the films by sulfur, showing that sulfur passivation provides a good method for improving of Cu2O-based devices.

The effects of ammonium sulfide surface treatment on electrodeposited p-type polycrystalline cuprous oxide (Cu2O) thin films deposited on Ti substrates were studied. The structural and morphological properties of the films were investigated using scanning electron microscopy, x-ray diffraction, and energy-dispersive x-ray spectroscopy. The changes in the conductivities and photocurrents of the films after the ammonium sulfide treatment were determined. Films that had undergone the ammonium sulfide treatment showed reduced resistivities, enhanced spectral photoresponses, and enhanced current-voltage characteristics. The results showed that ammonium sulfide treatment improved the peak output current of the p-type Cu2O films by about 400% compared with those of bare Cu2O films. This improvement is attributed to the passivation of defects in the films by sulfur, showing that sulfur passivation provides a good method for improving of Cu2O-based devices.
Keywords: Cuprous oxide; Thin films; Electrodeposition; Defects; Passivation; Spectral response